Determination the Risks Factors of Tuberculosis and Its Clinical Outcome during the Year (2022) in Al-Hilla City, Iraq - Sadiq Salam H. Al-Salih; Mohammed Malih Radhi; Nada Khazal Kadhim Hindi (Medical Journal of Babylon)
Background: Tuberculosis (TB) is an infectious disease caused by mycobacterium TB bacteria. Tuberculosis generally affects the lungs, but can also affect other parts of the body. The classic symptoms of active TB are a chronic cough with blood-containing mucus, fever, night sweats, and weight loss. Objectives: To determine the risks factors of tuberculosis and its clinical outcome in Hilla city and to determine the association between risks factors of tuberculosis and its clinical outcome. Materials and Methods: A descriptive study is conducted in Hilla City from periods September 1st 2021 to June 1st 2022. The sources of data are the TB patients’ medical records. A non-probability “purposive sample” of (N = 127) patients diagnosed with tuberculosis. The data were obtained retrospectively by reference to these cards. The medical records are in the form of cards and the information contained in them include demographic data of the patients (age, gender, smoking status, history of chronic diseases, and residency). Results: The results of study indicate that age group (21‐30) are have highest percentage between all age groups and men are more affected than women. Conclusion: The study concluded that the people who are male young adults and elderly, smoker and with chronic diseases are high risk factors for TB.